A comparative study of small voltage rectification circuits for implanted devices - Haider, Samnan; Mansor, Hasmah; Khan, Sheroz (IOP Publishing, 2013)
Biomedical implants have acquired an invulnerable and significant importance over the recent years due to their low voltage requirements and trifling dimensions. Biomedical implants are being widely employed for the continuous monitoring of intended parameters as well as stimulation of target organs in patient’s body. Being low power devices, the continuous powering without using battery dependent sources necessitates the alternative sources such as energy harvesting from the surroundings. Harvested output needs to be processed before using it for powering purposes, particularly in harsh and challenging premises. Even after processing, it needs to be made robust against the contiguous hazards so that maximum power is transferred to the load. A rectifier is employed to make this harvested energy usable. This paper compares the rectifier circuits, comparing their simulation output in terms of regulation, stability and power transferred. The rectification of small voltages is usually confronted by the threshold voltage drops that affect the output causing an effective drop in the power transfer efficiency and other parameters related. The solution to this problem has been suggested comparing the previous approaches with some modifications. Obtained results have been plotted in terms of ripple factor comparing them with the analytical calculations in order to show the role of capacitance in the reduction of ripple factor.